Perancangan Fasilitas Kerja yang Ergonomis Pada Stasiun Penyortiran CV Putra Darma - Haniza Haniza (Universitas Medan Area, 2019)
CV Putra Darma is a company engaged in the export industry of Arabica coffee. The process of coffee bean sorting is one of the production activities that consist in this industry. However, this action is still manually and un-ergonomic which still use the floor as a working medium. This facility may result the Musculoskeletal Disorders (MSDs) to the workers, particularly in the waist, legs, thighs, back, and neck. This study aims to design an ergonomic facility in coffee bean sorting process to avoid the MSDs, and that is work desk and work chair. At first step, the Standard Nordic Questionnaire was used to identify any MSDs from the workers, then to evaluate the actual condition of working posture, REBA method was employed in this study. The next step is to design this facility that is work desks and work chairs according to anthropometric data as much as 30 workers.